2023
DOI: 10.1111/1749-4877.12727
|View full text |Cite
|
Sign up to set email alerts
|

Developing fertility control for rodents: a framework for researchers and practitioners

Abstract: Fertility control is often heralded as a humane and effective technique for management of overabundant wildlife, including rodents. The intention is to reduce the use of lethal and inhumane methods, increase farm productivity and food security as well as reduce disease transmission, particularly of zoonoses. We developed a framework to guide researchers and stakeholders planning to assess the effectiveness of a potential contraceptive agent for a particular species. Our guidelines describe the overarching rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 136 publications
0
6
0
Order By: Relevance
“…2022; Massei et al. 2023). Sidhu and Singla (2023) showed that the consumption of quinestrol alone for 10 days by male lesser bandicoot rats, Bandicota bengalensis , in the laboratory reduced their fertility for more than 30 days, with partial reversibility by 60 days.…”
Section: Re‐emergence Of Interest In Fertility Controlmentioning
confidence: 99%
See 4 more Smart Citations
“…2022; Massei et al. 2023). Sidhu and Singla (2023) showed that the consumption of quinestrol alone for 10 days by male lesser bandicoot rats, Bandicota bengalensis , in the laboratory reduced their fertility for more than 30 days, with partial reversibility by 60 days.…”
Section: Re‐emergence Of Interest In Fertility Controlmentioning
confidence: 99%
“…From the outset, a strong understanding of the pathway to potential success is essential-the selection of the fertility control agent is simply the beginning of a long, resource-intensive, and iterative program of laboratory, enclosure, and multi-year field studies. In parallel, regulatory and governance issues as well as public acceptance must be a consistent part of the conversation (Massei et al 2023). Two papers focused more specifically on recent results assessing the effects of synthetic steroids, either a combination of synthetic estrogen (quinestrol) and progesterone (EP-1), or quinestrol alone.…”
Section: Fertility Controlmentioning
confidence: 99%
See 3 more Smart Citations